Sistemática e biogeografia de Labrundinia Fittkau, 1962 (Diptera: Chironomidae : Tanypodinae): uma abordagem morfológica e molecular - Silva, Fabio Laurindo da (2012)
This doctoral research focused on the systematics and biogeography of the Labrundinia species (Insecta: Diptera: Chironomidae: Tanypodinae). The basis of this study rested on the examination of the type material of all previously described Labrundinia species, including species deposited in national and foreign museums. Field work were carried out to collect more specimens and to secure associations between larvae, pupae and adults. In this study 14 known species of Labrundinia were redescribed and 25 new species were described from the Neotropical region. Morphological and molecular analyses were conducted to infer phylogenetic relationships among all species of the genus and identification keys were developed for all life stages. Based on the results of the phylogeny and distribution of the species, a biogeographic analysis was performed to provide the most probable biogeographic history for the group. The interpretations of the phylogenetic results indicate Labrundinia as a monophyletic group. The group is shown in all resulting trees. Based on these phylogenetic reconstructions, biogeographical analyses were run and indicated Labrundinia ancestor as having its initial diversification in the Neotropical region.